2003
DOI: 10.1074/jbc.m209008200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Xenopus Galectin Family

Abstract: We have isolated six novel galectin cDNAs from a Xenopus laevis kidney cDNA library. The newly identified X. laevis galectins (xgalectins) comprise one proto type (xgalectin-Vb), one chimera type (xgalectin-VIIa), and four tandem repeat types (xgalectin-IIb, -IIIb, -VIa, and -VIIIa). Thus, together with those mentioned in our previous work (Shoji, H., Nishi, N., Hirashima, M., and Nakamura, T. (2002) Glycobiology 12, 163-172), the 12 xgalectins are classified into three types based on their domain structures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 39 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…By qPCR, we found that Pl - gal-8 transcripts showed a developmental upregulation at gastrula and pluteus stages. This finding is in accordance with the important role attributed to galectins in controlling morphogenetic events during embryogenesis 36 and particularly with the role assigned to carbohydrates and carbohydrate-bearing molecules in supporting cell-cell interactions during sea urchin gastrulation 37 . For example, the binding of secondary mesenchyme cells to the blastocoel roof is prevented by D-mannose like residues, resulting in the inhibition of gastrulation 37 .…”
Section: Discussionsupporting
confidence: 88%
“…By qPCR, we found that Pl - gal-8 transcripts showed a developmental upregulation at gastrula and pluteus stages. This finding is in accordance with the important role attributed to galectins in controlling morphogenetic events during embryogenesis 36 and particularly with the role assigned to carbohydrates and carbohydrate-bearing molecules in supporting cell-cell interactions during sea urchin gastrulation 37 . For example, the binding of secondary mesenchyme cells to the blastocoel roof is prevented by D-mannose like residues, resulting in the inhibition of gastrulation 37 .…”
Section: Discussionsupporting
confidence: 88%
“…All the fluorescein-tagged saccharides have previously been described (19). Plasmids encoding human galectin-3 in pET-3c were as described (34), Xenopus galectin-3 (galectin VIIa (35)) in pET-11a was kindly provided by Dr. Hiroki Shoji, Kagawa University, Japan, and mouse galectin-3 in pIN III ompA2 (36) was kindly provided by Professor John L. Wang, Michigan State University.…”
Section: Methodsmentioning
confidence: 99%
“…Most metazoans are endowed with a complex galectin repertoire, with members exhibiting multiple isoforms 53 and subtle variations in carbohydrate specificity. This, together with the plasticity observed in sugar binding 47 , suggests that there is substantial diversity in their glycan-recognition properties.…”
Section: Galectins: Structure–function Relationshipsmentioning
confidence: 99%